Deployment Status and Child Neglect Types in the U.S. Army. (February 2018) - Cozza, Stephen J.; Whaley, Gloria L.; Fisher, Joscelyn E.; Zhou, Jing; Ortiz, Claudio D.; McCarroll, James E.; Fullerton, Carol S.; Ursano, Robert J.
Increases in combat deployments have been associated with rises in rates of child neglect in U.S. military families. Although various types of child neglect have been described in military families, it is unknown whether deployment status is associated with specific types of child neglect and whether other factors, such as substance misuse, play a role. To determine the contribution of service member deployment status to the risk of specific child neglect types, data were collected from 390 substantiated U.S. Army child neglect case files. The contributions of deployment status at the time of the neglect incident and parental alcohol or drug-related misuse to risk of neglect types were examined controlling for military family rank and child age. Compared to never deployed families, families with a service member concurrently deployed at the time of the neglect incident were at higher risk for failure to provide physical needs, lack of supervision, and educational neglect, but at lower risk for emotional neglect. Being previously deployed incurred risk for moral–legal neglect. Substance misuse added risk for moral–legal and educational neglect. Findings indicate the need for tailored prevention strategies to target different periods within the deployment cycle.